IMPLIKASI TEOLOGIS TENTANG HUKUM ROH YANG MEMERDEKAKAN DARI HUKUM DOSA DAN HUKUM MAUT DALAM ROMA 8:2 - Putri, Agustin Soewitomo (Shift Key : Jurnal Teologi dan Pelayanan, 2020)
Mankind has fallen into sin and lost the glory of God. The fall of man into sin made man have a tendency to sin. This is what is called the law of sin and death. The law of death follows the law of sin. The two laws are closely related. Humans need the antithesis of the law of sin and death. Romans 1-8 leads people to the law of the Spirit. The law of the Spirit is great news in the midst of mankind's struggle to experience victory over sin and death.